Pengaruh Size KAP dan Audit Capacity Stress terhadap Kualitas Audit - Pasya, Qayla Damara (Jurnal KIAFE, 2025)
This study aims to analyze the effects of Public Accounting Firm (KAP) size and audit capacity stress on audit quality in banking sector companies listed on the Indonesia Stock Exchange (IDX). KAP size reflects the capacity and reputation of audit institutions, while audit capacity stress represents auditor workload pressure that may influence independence and audit thoroughness. This study employs a quantitative approach using panel data regression analysis for the 2021–2023 period. The sample was selected using purposive sampling and consists of 35 banking companies, resulting in 105 firm-year observations. Data were analyzed using the Common Effect Model (CEM) regression approach with EViews 12. Audit quality was measured using the Modified Jones Model, while KAP size was measured using a dummy variable and audit capacity stress was measured based on the ratio of banking clients audited by a KAP to the number of partners in the KAP. The results indicate that KAP size has a positive and significant effect on audit quality, whereas audit capacity stress has no significant effect on audit quality. These findings suggest that institutional reputation and audit firm capacity play a more dominant role than workload pressure in determining audit quality in the Indonesian banking sector.